RF Spiral planar inductor designs-preliminary results - 188853 See, Guan Huei; Mazlina Esa; Albert Victor Kordesh; Asia Pacific Conference on Applied Electromagnetics (2003 : Shah Alam, Selangor) (Skudai : Universiti Teknologi Malaysia, 2003)
16